2003
DOI: 10.1016/j.solmat.2003.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of rough electrochromic phosphotungstic acid films obtained by spray-gel process

Abstract: Rough electrochromic phosphotungstic acid (PWA) films were fabricated by spraying a gel of phosphotungstate anions with a molar ratio of P:W = 1:12 onto glass substrates precoated with transparent and electrically conducting SnO 2 :F at 300 °C. The analysis by X-ray photoelectron spectroscopy (XPS) determined that the P:W molar ratio in the films was approximately 1:14. Infrared spectroscopy (IR) and X-ray diffraction (XRD) showed that the film is a polycrystalline phosphotungstic acid. SEM micrographs showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…[2] Figure 2. (a) WO 3 as example for cathodic electrochromism, [18][19][20][21][22][23][24][25] (b) PANI as an example for anodic electrochromism. [8][9][10][11][12][13] tungsten-containing solution.…”
Section: Electrochromic Coatings Based On Tungsten Trioxidementioning
confidence: 99%
“…[2] Figure 2. (a) WO 3 as example for cathodic electrochromism, [18][19][20][21][22][23][24][25] (b) PANI as an example for anodic electrochromism. [8][9][10][11][12][13] tungsten-containing solution.…”
Section: Electrochromic Coatings Based On Tungsten Trioxidementioning
confidence: 99%
“…From the slope of the curve of the cathodic/anodic peak current versus square root of scan rates in the linear part, the diffusion coefficients were calculated. For PTA it is found to be 9.49 × 10 −11 cm 2 /sec and 6.96 × 10 −11 cm 2 /sec for intercalation and deintercalation process, respectively and for TlPTA it is found to be 4.8 × 10 −10 cm 2 /sec and 6.09 × 10 −11 cm 2 /sec for intercalation and deintercalation process, respectively [(normalH3PnormalO4) (normalW6+ normalO3)12]+x Lnormali++xnormale [Lnormalinormalx(normalH3PnormalO4)(normalW5+normalO3)12]PTA (colorless) ...…”
Section: Resultsmentioning
confidence: 99%
“…For PTA it is found to be 9.49 Â 10 À11 cm 2 /sec and 6.96 Â 10 À11 cm 2 /sec for intercalation and deintercalation process, respectively and for TlPTA it is found to be 4.8 Â 10 À10 cm 2 /sec and 6.09 Â 10 À11 cm 2 /sec for intercalation and deintercalation process, respectively. [12,13] Cyclic Voltammetry (CV) for Testing of Durability of Phophotungstic Acid (PTA) and Tl þ Intercalated Phophotungstic Acid Thin Films Figure 2a and b shows CV spectra recorded for phophotungstic acid (PTA) and Tl þ intercalated phosphotungstic acid (Tl 3 PO 4 ) (WO 3 ) 12 thin films for its 100 th , 200 th , 500 th and 1000 th cycle. From the figures, it was observed that with an increase in number of cycle threshold voltage (Et), the voltage corresponding to rapid surge of Li þ ions in to the phosphotungstic acid (PTA) and Tl þ intercalated phosphotungstic acid Tl 3 (PO 4 ) (WO 3 ) 12 film shifts anodically.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such work has been reported for oxides based on tungsten, iridium, vanadium, and nickel. W oxide colours under charge insertion and is referred to as a cathodic electrochromic materials, whereas oxides of Ir and Ni colour under charge & W oxide films have been prepared by evaporation [28 -31], sputtering [32,33], spray pyrolysis [34], sol -gel deposition [35 -40], and electrodeposition [41,42]; work has been reported also on W oxide containing Mo (made by chemical vapour deposition [43] and electrodeposition [44]), V (made by sputtering [45]), Ta (made by pulsed laser ablation [46]), Ti (made by electrodeposition [47] and spin coating followed by a templating technique [48]), and P (made by sol -gel deposition [49]); & Ir oxide films have been prepared by electrodeposition [50,51]; work has been reported also on Ir oxide containing and Ta (made by sputtering [52]); & V oxide films have been prepared by sputtering [53]; work has been reported also on such films with polymer additives [54]; and & Ni oxide films have been prepared by reactive evaporation [55], pulsed laser deposition [56], sol -gel deposition [57,58], and electrodeposition [59]; work has been reported also on such sputter-deposited films containing Mg, Al, Si, V, Zr, Nb, Ag, Ta [60] as well as Au [61].…”
Section: Review Of Current Work On Inorganic Electrochromic Filmsmentioning
confidence: 99%